2016
DOI: 10.4085/1062-6050-51.12.05
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Mechanical Work at the Knee and Ankle Joints During Fast Running in Minimalist Shoes

Abstract: Context: Minimalist shoes have been suggested as a way to alter running biomechanics to improve running performance and reduce injuries. However, to date, researchers have only considered the effect of minimalist shoes at slow running speeds.Objective: To determine if runners change foot-strike pattern and alter the distribution of mechanical work at the knee and ankle joints when running at a fast speed in minimalist shoes compared with conventional running shoes.Design: Crossover study. Setting: Research lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
(44 reference statements)
5
20
1
Order By: Relevance
“…Our results suggested that the amplitude of the negative power of the knee joint was similar between training shoes and racing flats, whereas the duration of the negative power of the knee joint was longer for training shoes than for racing flats. Previous studies showed similar results and reported that the negative work and power of the knee joint was greater for training shoes than for minimalist shoes [18,31]. Furthermore, the present results revealed that the moment and the angular velocity of the knee joint were not different between training shoes and racing flats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results suggested that the amplitude of the negative power of the knee joint was similar between training shoes and racing flats, whereas the duration of the negative power of the knee joint was longer for training shoes than for racing flats. Previous studies showed similar results and reported that the negative work and power of the knee joint was greater for training shoes than for minimalist shoes [18,31]. Furthermore, the present results revealed that the moment and the angular velocity of the knee joint were not different between training shoes and racing flats.…”
Section: Discussionsupporting
confidence: 86%
“…However, the influence of the different types of running shoes on the negative work of each lower extremity joint and mechanical interpretation using associated kinetic and kinematic parameters remain unclear. Several studies reported [6,18,23,33] that joint kinetic and kinematic parameters were not necessarily decreased by using running shoes with thick midsoles compared to those with thin midsoles. The purpose of this study, therefore, was to examine the differences in the negative work and associated kinetic and kinematic parameters of each lower extremity joint between training shoes and racing flats during the contact phase of running.…”
Section: Training Shoes Do Not Decrease the Negative Work Of The Lowementioning
confidence: 99%
“…The term "load distribution" refers to how the load per stride is distributed across individual anatomical structures (eg, joint surfaces, muscles, and ligaments). Using a few examples, load distribution is affected by (a) Changing running shoes, as the load may be distributed differently across lower extremities, 36,37,[40][41][42][43][44][45][46][47][48] (b) applying a different running technique, as differences in kinematic and kinetic characteristics between foot-strike patterns were found during running. 49 Other technique modifications influencing running kinematics and/or kinetics involve trunk posture, 50 step rate, 39,51,52 the pose-method and chi-running, [53][54][55] and step length 56 ; (c) change in terrain, as uphill and downhill running will change certain kinematics and hence load distribution depending on the nature of the terrain 57 ; (d) changing between overground and treadmill, as loads are distributed differently in the two settings, 38 (e) changing surface, as surface hardness may influence the interplay of load distribution to the lower extremity by changing the lower leg kinematics and kinetics during running [58][59][60][61] ; and (f) bone morphology and physiology, as the form and structure and special structural features of the leg impacts how the load is distributed.…”
Section: Load Distribution Per Stridementioning
confidence: 99%
“…Indeed, a recent study demonstrated increased energy absorption and generation at the ankle joint in runners who made subtle changes to foot landing position (contact angle changed from 7.4° to 2.4° dorsi-flexion) when running in minimalist shoes. 11 Similarly, another study demonstrated increased intrinsic foot muscle cross-sectional area in runners who changed contact angle from 8.6° to 2.7° dorsiflexion during 12 weeks of minimalist shoe training. 24 Increased energy absorption and generation at the ankle joint and increased intrinsic foot muscle strength have been proposed as mechanisms for improving elastic-energy storage and recovery in the Achilles' tendon 11 and arch of the foot.…”
Section: Discussionmentioning
confidence: 97%
“…18 The Asics Piranha has been shown to cause running kinematic changes that are typical of minimalist shoes. 11 Body mass was assessed before each assessment of running economy. Participants then completed a 5-minute warm-up on a motorised treadmill (Model 645, Quinton Instrument Co., WA, USA) set to a comfortable jogging speed of 8 km•h -1 .…”
Section: Methodsmentioning
confidence: 99%